1996
DOI: 10.1111/j.1651-2227.1996.tb14220.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal intestinal permeability in children with autism

Abstract: We determined the occurrence of gut mucosal damage using the intestinal permeability test in 21 autistic children who had no clinical and laboratory findings consistent with known intestinal disorders. An altered intestinal permeability was found in 9 of the 21 (43%) autistic patients, but in none of the 40 controls. Compared to the controls, these nine patients showed a similar mean mannitol recovery, but a significantly higher mean lactulose recovery (1.64% +/- 1.43 vs 0.38% +/- 0.14; P < 0.001). We speculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
183
2
7

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(196 citation statements)
references
References 1 publication
4
183
2
7
Order By: Relevance
“…4,5 Several lines of evidence suggest that autism should be viewed as a multiorgan systemic disorder with a prenatal onset. On one hand, autism does not solely affect the central nervous system (CNS), despite encompassing obvious neurodevelopmental components: systemic signs and symptoms include macrosomy, 6 excessive intestinal permeability and nonspecific enterocolitis, [7][8][9] immune dysreactivity 9 and renal oligopeptiduria. 10 On the other hand, the neurodevelopmental mechanisms underlying the CNS abnormalities found in postmortem studies, which include reduced programmed cell death and/ or increased cell proliferation, and altered neuronal migration, differentiation and synaptogenesis, with the exception of the latter, are all active prenatally, especially during the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Several lines of evidence suggest that autism should be viewed as a multiorgan systemic disorder with a prenatal onset. On one hand, autism does not solely affect the central nervous system (CNS), despite encompassing obvious neurodevelopmental components: systemic signs and symptoms include macrosomy, 6 excessive intestinal permeability and nonspecific enterocolitis, [7][8][9] immune dysreactivity 9 and renal oligopeptiduria. 10 On the other hand, the neurodevelopmental mechanisms underlying the CNS abnormalities found in postmortem studies, which include reduced programmed cell death and/ or increased cell proliferation, and altered neuronal migration, differentiation and synaptogenesis, with the exception of the latter, are all active prenatally, especially during the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…26 This effect, linking calcium, 65 oxidative stress, 57 and PKCb to the stability of epithelial cytoskeleton in the gut, could conceivably explain the abnormally elevated intestinal permeability present in many autistic patients and the subsequent activation of the immune system due to the absorption of the first foreign dietary peptides recognized by the gut immune system as 'non-self', namely casein and gluten. 7 Our current phenotypic data set does not allow us to directly test this hypothesis. Nonetheless, our sample encompasses 106 families with mixed genotypes at SNP rs3785392, 7 families whose members all carry the 'normal' 1/1 genotype, and 10 families entirely composed of 2/2 'risk genotype' carriers.…”
mentioning
confidence: 99%
“…Speculation centred on a possible role for the gut mucosal barrier as playing some part in this process (42) . Drawing again on the example of CD, where modified gluten peptides are able to gain access to the lamina propia, part of the gut mucosa, the suggestion was that abnormal porosity of the intestinal barrier may facilitate transport of these opioid peptides (43) or their effects into the wider central nervous system.…”
Section: Increased Intestinal Permeabilitymentioning
confidence: 99%
“…Leaky gut hypotheses (10)(11)(12)(13) have suggested that differences in gut permeability lead to opioid excess and, thus, neuropsychiatric abnormalities, as well as causing malabsorption and metabolic abnormalities such as methylmalonic aciduria. Although D'Eufemia et al (14) have also discussed leaky guts in autism, there are no further data to support the impact of a leaky gut on behavioural abnormalities. There is also no evidence for Wakefield's previous claims about a measles link to inflammatory bowel disease (IBD) (15) that caused years of concern for that population until failure of replication refuted his claims (16).…”
Section: Measles and 'Leaky Gut'mentioning
confidence: 99%